Investigation on the effect of alkyl chain linked mono-thioureas as Jack bean urease inhibitors, SAR, pharmacokinetics ADMET parameters and molecular docking studies - Larik, Fayaz Ali; Faisal, Muhammad; Saeed, Aamer; Channar, Pervaiz Ali; Korabecny, Jan; Jabeen, Farukh; Mahar, Ihsan Ali; Kazi, Mehar Ali; Abbas, Qamar; Murtaza, Ghulam; Khan, Gul Shahzada; Hassan, Mubashir; et al. (Bioorganic chemistry, 2019)
The increasing resistance of pathogens to common antibiotics, as well as the need to control urease activity to improve the yield of soil nitrogen fertilization in agricultural applications, has stimulated the development of novel classes of molecules that target urease as an enzyme. In this context, the newly developed compounds on the basis of 1-heptanoyl-3-arylthiourea family were evaluated for Jack bean urease enzyme inhibition activity to validate their role as potent inhibitors of this enzyme. 1-Heptanoyl-3-arylthioureas were obtained in excellent yield and characterized through spectral and elemental analysis. All the compounds displayed remarkable potency against urease inhibition as compared to thiourea standard. It was found that novel compounds fulfill the criteria of drug-likeness by obeying Lipinski's rule of five. Particularly compound 4a and 4c can serve as lead molecules in 4D (drug designing discovery and development). Kinetic mechanism and molecular docking studies also carried out to delineate the mode of inhibition and binding affinity of the molecules.
Keywords: kinetika; Acyl thioureas; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Kinetic mechanism; Urease; simulace molekulového dockingu; Jack bean urease; inhibitory enzymů; Molecular Docking Simulation; ureasa; Lipinski’s rules; Thiourea; Molecular modeling; Canavalia; vztahy mezi strukturou a aktivitou; Kinetics; molekulární struktura; thiomočovina; Structure-Activity Relationship; Enzyme Inhibitors; Molecular Structure; Antioxidant